Furyl high-molecular polyester with excellent toughness and preparation method of furyl high-molecular polyester
By replacing FDCA with FDME and using low-temperature esterification and solid-phase tackification methods, the problems of low esterification efficiency and yellowing of slices during high-temperature esterification of PBF are solved, and high-strength high-strength furyl polymer polyester with high molecular weight and color are achieved efficiently.
Patent Information
- Application Number
- CN202411933147.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
AI Technical Summary
During the high-temperature esterification of PBF, FDCA is prone to decarboxylation, and BDO itself cyclization and dehydration produces by-products, resulting in a decrease in esterification efficiency, an increase in production costs, and the obtained PBF slices are yellowed.
FDME is used instead of FDCA, and the reaction temperature and time are controlled through preliminary low-temperature esterification, melt polymerization, and the reaction temperature and time are obtained, and the molecular weight is increased by solid phase viscosity to obtain high-toughness furanyl polymer polyester with high molecular weight and color improvement.
The esterification reaction efficiency is improved, the FDCA decarboxylation rate is reduced, the by-product generation is reduced, and the color and mechanical properties of PBF slices are significantly improved.
Smart Images

Figure CN119613689A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer polymerization, and in particular relates to a furan-based polymer polyester with excellent toughness and a preparation method thereof. Background Art
[0002] Polyester is a common polymer in life. It occupies 80% of the market share in the chemical fiber industry and is widely used in bottles, films, etc. It is widely used in packaging, medical and health, construction, electronic appliances, automobiles and other fields. Among them, PET (polyethylene terephthalate)
[0003] ) and PBT (polybutylene terephthalate) are the fastest growing. With the development of society, its demand is gradually increasing. Its main monomer PTA is non-renewable, so it is very important to improve the utilization rate of materials and find green and renewable energy.
[0004] PBF (polybutylene 2,5-furandicarboxylate) is usually obtained by melt polymerization of FDCA (2,5-furandicarboxylic acid) and BDO (butanediol). It has good physical and mechanical properties, and some of its properties are similar to PBT, and it can be used as a substitute in some aspects. Its reaction monomer FDCA can be further oxidized by dehydrating fructose glucose to generate HMF (5-hydroxymethylfurfural). BDO can be obtained by direct fermentation of glucose and indirectly by hydrogenation of succinic acid, and can also be derived from biomass, so PBF can be 100% biomass-derived.
[0005] However, during the high-temperature esterification process of PBF, FDCA is prone to decarboxylation and BDO is self-cyclized and dehydrated to produce tetrahydrofuran, so its esterification efficiency is greatly reduced, and the production cost is also increased. In addition, due to factors such as the increase in by-products, the PBF slices obtained are yellowed. Therefore, it is necessary to improve the existing process and propose a new preparation method for furan-based polymer polyester. Summary of the invention
[0006] In view of the above problems, the present invention provides a method for preparing a furan-based high molecular weight polyester with excellent toughness, using FDME (2,5-furandicarboxylic acid methyl ester) instead of FDCA, and the direct byproduct is methanol, which is easier to discharge. Due to the lower esterification temperature, the cyclization rate of BDO itself is reduced, the esterification reaction efficiency is improved, and the decarboxylation rate of FDCA is greatly reduced, thereby solving the above technical problems existing in the existing process. Specifically, by preliminary low-temperature esterification and melt polymerization, the reaction temperature and time are controlled to obtain a furan ring polyester with a low molecular weight, and then the molecular weight of the slice is increased by solid phase viscosity enhancement, and finally a high molecular weight and high-toughness furan-based high molecular weight polyester with improved color is obtained.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a furan-based high molecular weight polyester with excellent toughness comprises the following steps:
[0009] S1: preparing low molecular weight furan ring polyester; specifically:
[0010] S11: adding a certain amount of furan ring-containing dibasic lipid and aliphatic diol as raw materials into a reaction container, adding an antioxidant and a catalyst, purging with nitrogen, and heating to 130-190° C. and stirring evenly, and maintaining a rotation speed of 80-120 rpm;
[0011] S12: maintaining the temperature, reacting for 0.5-3h and maintaining the esterification under normal pressure, and collecting the obtained esterification liquid;
[0012] S13: When the weight of the obtained esterified liquid reaches 1.5-3.2 times of the theoretical liquid output, the esterification is completed;
[0013] S14: Start to evacuate the air, the pressure is less than -8KPa within 5 minutes and the evacuation is continued. After the pressure is evacuated to below -100Pa, the temperature is raised to 200-240℃;
[0014] S15: maintaining the vacuum less than -70 Pa, reacting for 2-4 hours, reducing the speed to 10-30 rpm and reacting for 10-20 minutes, introducing nitrogen to a weak positive pressure after the reaction, discharging, cutting and drying to obtain a furan ring polyester with a lower molecular weight;
[0015] S2: Preparation of high molecular weight furan ring polyester by solid phase viscosity enhancement; specifically:
[0016] The furan ring polyester with a lower molecular weight obtained in step S1 is added to a reaction kettle. Under certain temperature and rotation speed conditions, an inert gas is continuously introduced, and the temperature is consistent with the temperature in the kettle. The reaction is carried out for 10-24 hours. After the discharge is cooled, a furan ring polyester with a higher molecular weight is obtained.
[0017] Furthermore, the furan ring-containing dibasic lipid is one of 2,5-furandicarboxylic acid methyl ester and 3,4-furandicarboxylic acid methyl ester.
[0018] Furthermore, the aliphatic diol is one or a mixture of ethylene glycol, propylene glycol, butylene glycol and hexylene glycol.
[0019] Furthermore, the antioxidant is one of 168, 626, B215, 1010, 1098 or a combination thereof.
[0020] Furthermore, the catalyst is one or more of triphenyl phosphite, titanium glycol, zinc acetate, phosphoric acid, phosphorous acid, and phosphate.
[0021] Furthermore, in step S11, the molar ratio of the aliphatic diol to the furan ring-containing dibasic lipid substance is (1.2-2.5):1.
[0022] Furthermore, in step S11, the amount of the antioxidant is 0.1-5‰ based on the weight ratio of the furan ring-containing dibasic lipid; the amount of the catalyst is 0.1-5% based on the weight ratio of the furan ring-containing dibasic lipid.
[0023] Furthermore, in step S2, the temperature and rotation speed conditions are: 120-180° C. and 80-120 rpm.
[0024] Furthermore, in step S2, the inert gas is nitrogen at a rate of 5-8 L / min.
[0025] On the other hand, the present invention also provides a furan-based high molecular polyester with excellent toughness obtained by the above preparation method.
[0026] The present invention uses furan ring-containing dibasic lipids and aliphatic diols as raw materials, and provides a preparation method for preparing low molecular weight furan ring polyester by low-temperature esterification at normal pressure and melt polymerization, and then obtaining furan bio-based polyester by solid phase viscosity enhancement. The obtained furan ring polyester has a large molecular weight, improved color, and good thermal stability and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the thermogravimetric diagram of the prepared PBF;
[0028] Figure 2 This is the secondary heating curve of the PBF-DSC obtained. DETAILED DESCRIPTION
[0029] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0030] Preparation Example of Furan Ring Polyester
[0031] Example 1
[0032] 700g of methyl 2,5-furandicarboxylate, 549g of butanediol, 2.1g of triphenyl phosphite and 0.7g of B215 were added to the reactor. After the feeding was completed, the reactor was sealed and high-purity nitrogen was introduced into the reactor. The process was repeated 1-3 times to exhaust the air in the reactor and then return to normal pressure to provide a reaction environment. Stirring at 150°C (speed 120rpm), uniformly mixing and continuing the reaction for 3h, collecting the obtained esterified liquid to 2 times the theoretical liquid output to terminate the esterification (the theoretical liquid output can be measured by 2,5-furandicarboxylic acid The amount of methyl ester is calculated); vacuuming is started, and the pressure is less than -8 kpa within 5 minutes, and then vacuuming is slowly done (0.01 MPa / min). After the vacuum reaches -100 Kpa, the temperature is raised to 220°C, and the vacuum degree is maintained at ≤-70 Kpa. After the reaction is maintained for 2.5 hours, the speed is reduced to 20 rpm, and the reaction is ended after 15 minutes, and stirring is stopped. Nitrogen is introduced into the kettle to 0.1 MPa, and the material is discharged, cut, and dried to obtain all-bio-based furan ring polyester particles with a low molecular weight.
[0033] Embodiment 1-11:
[0034]
[0035]
[0036]
[0037]
[0038]
[0039] The solid phase adhesion process of Example 1-11 is as follows:
[0040] Take furan ring polyester with lower molecular weight and add it into the reactor. At 150℃ and 100rpm, inert gas is continuously introduced. The temperature is consistent with the temperature in the reactor (N2 is used as protective gas considering the cost). The rate is 6L / min and the reaction is carried out for 12h. After discharging, furan ring polyester with higher molecular weight is obtained.
[0041] Embodiment 12-15:
[0042] The preparation of low molecular weight furan ring polyester is the same as in Example 1, and the parameters of the solid phase viscosity enhancement process are changed as follows:
[0043] Example Temperature(℃) Nitrogen rate (L / min) Reaction time (h) 12 130 6 12 13 180 6 12 14 150 6 8 15 150 6 20
[0044] Comparative Example 1:
[0045] 700g of methyl 2,5-furandicarboxylate, 549g of butanediol, 2.1g of triphenyl phosphite and 1.05g of B215 were added to a reactor. After the feeding was completed, the reactor was sealed and high-purity nitrogen was introduced into the reactor. The reaction was repeated 1-3 times to exhaust the air in the reactor and then to provide a reaction environment at normal pressure; the reactor was stirred at 150°C (rotation speed 120rpm), uniformly mixed and reacted for 3h, and the esterification liquid obtained was collected to reach 2 times of the theoretical liquid output to terminate the esterification; vacuuming was started, and the pressure was less than -8kpa within 5min, and then vacuuming was slowly carried out (0.01Mpa / min). After the vacuum reached -100Kpa, the temperature was raised to 220°C, and the vacuum degree was maintained at ≤-70Kpa. After the reaction was maintained for 2.5h, the rotation speed was reduced to 20rpm, and the reaction was terminated after 15min, and the stirring was stopped. Nitrogen was introduced into the reactor to 0.1Mpa, and the furan-based polyester particles with a low molecular weight were obtained after discharging, cutting and drying.
[0046] Comparative Example 2:
[0047] 700g of methyl 2,5-furandicarboxylate, 549g of butanediol, 2.1g of triphenyl phosphite and 1.05g of B215 were added to a reactor. After the feeding was completed, the reactor was sealed, and high-purity nitrogen was introduced into the reactor. The reaction was repeated 1-3 times to exhaust the air in the reactor and then to provide a reaction environment at normal pressure; the reactor was stirred at 150°C (rotation speed 120rpm), uniformly mixed and reacted for 3h, and the esterification liquid obtained was collected to reach 2 times the theoretical liquid output to end the esterification; vacuuming was started, and the pressure was less than -8kpa within 5min, and then vacuuming was slowly done (0.01Mpa / min). After the vacuum reached -100Kpa, the temperature was raised to 220°C, and the vacuum degree was maintained at ≤-70Kpa. After the reaction was maintained for 4h, the rotation speed was reduced to 20rpm, and the reaction was ended after 15min, and the stirring was stopped. Nitrogen was introduced into the reactor to 0.1Mpa, and the furan-based polyester particles with a low molecular weight were obtained after discharging, cutting and drying.
[0048] Comparative Example 3:
[0049] 594g 2,5-furandicarboxylic acid, 549g butanediol, 1.8g triphenyl phosphite and 0.6g B215 were added to the reactor. After the feeding was completed, the reactor was sealed and high-purity nitrogen was introduced into the reactor. The reaction was repeated 1-3 times to exhaust the air in the reactor and then to provide a reaction environment at normal pressure; the reactor was stirred at 150°C (rotation speed 120rpm), uniformly mixed and reacted for 5h, and the esterification liquid obtained was collected to reach 2 times the theoretical liquid output to end the esterification; vacuuming was started, and the pressure was less than -8kpa within 5min, and then vacuuming was slowly done (0.01Mpa / min). After the vacuum reached -100Kpa, the temperature was raised to 220°C, and the vacuum degree was maintained at ≤-70Kpa. After the reaction was maintained for 2.5h, the rotation speed was reduced to 20rpm, and the reaction was ended after 15min, stirring was stopped, nitrogen was introduced into the reactor to 0.1Mpa, the material was discharged, and pelletized to obtain furan ring polyester particles with extremely low viscosity, which were not subjected to the next step of treatment.
[0050] Comparative Example 4:
[0051] 594g 2,5-furandicarboxylic acid, 960g butanediol, 1.8g triphenyl phosphite and 0.6g B215 were added to the reactor. After the feeding was completed, the reactor was sealed and high-purity nitrogen was introduced into the reactor. The reaction was repeated 1-3 times to exhaust the air in the reactor and then to provide a reaction environment at normal pressure; the reactor was stirred at 190°C (rotation speed 120rpm), uniformly mixed and reacted for 3h, and the esterification liquid obtained was collected to reach 3 times of the theoretical liquid output to end the esterification; vacuuming was started, and the pressure was less than -8kpa within 5min, and then vacuuming was slowly done (0.01Mpa / min). After the vacuum reached -100Kpa, the temperature was raised to 220°C, and the vacuum degree was maintained at ≤-70Kpa. After the reaction was maintained for 2.5h, the rotation speed was reduced to 20rpm, and the reaction was ended after 15min, and the stirring was stopped. Nitrogen was introduced into the reactor to 0.1Mpa, and the furan-based polyester particles with a low molecular weight were obtained after discharging, cutting and drying.
[0052] Take furan ring polyester with lower molecular weight and add it into the reactor. At 150℃ and 100rpm, inert gas is continuously introduced. The temperature is consistent with the temperature in the reactor (N2 is used as protective gas considering the cost). The rate is 6L / min and the reaction is carried out for 12h. After discharging, furan ring polyester with higher molecular weight is obtained.
[0053] Comparative Example 5:
[0054] 594g 2,5-furandicarboxylic acid, 960g butanediol, 1.8g triphenyl phosphite and 0.6g B215 were added to the reactor. After the feeding was completed, the reactor was sealed and high-purity nitrogen was introduced into the reactor. The reaction was repeated 1-3 times to exhaust the air in the reactor and then to provide a reaction environment at normal pressure; the reactor was stirred at 190°C (rotation speed 120rpm), uniformly mixed and reacted for 3h, and the esterification liquid obtained was collected to reach 3 times of the theoretical liquid output to end the esterification; vacuuming was started, and the pressure was less than -8kpa within 5min, and then vacuuming was slowly done (0.01Mpa / min). After the vacuum reached -100Kpa, the temperature was raised to 220°C, and the vacuum degree was maintained at ≤-70Kpa. After the reaction was maintained for 2.5h, the rotation speed was reduced to 20rpm, and the reaction was ended after 15min, and the stirring was stopped. Nitrogen was introduced into the reactor to 0.1Mpa, and the furan-based polyester particles with a low molecular weight were obtained after discharging, cutting and drying.
[0055] Take furan ring polyester with lower molecular weight and add it into the reactor. At 150℃ and 100rpm, continuously introduce inert gas. The temperature is consistent with the temperature in the reactor (N2 is used as protective gas considering the cost). The rate is 6L / min. React for 24h and obtain furan ring polyester with higher molecular weight after discharging.
[0056] Furan ring polyester test results
[0057]
[0058]
[0059]
[0060] (Note: Example 2 and Example 10 are unsuccessful examples, no PBF product was obtained, so there is no relevant data)
[0061] Intrinsic viscosity test: refer to GB / T 14190-2017 to test the intrinsic viscosity of the sample.
[0062] Thermal gravimetric test: The thermal decomposition performance of the obtained samples was tested using a TGA thermogravimetric analyzer. 5-10 mg of the sample was weighed and heated from 50°C to 700°C under a nitrogen atmosphere (20 ml / min).
[0063] Differential Scanning Calorimetry: The obtained samples were subjected to thermal analysis tests using a differential scanning calorimeter (DSC). The test temperature range was 30°C-230°C. Weigh 5-10 mg of the sample, and in a nitrogen atmosphere (20 ml / min), heat from 30°C to 230°C at 10°C / min, isotherm for 5 min; cool to 30°C at 10°C / min, isotherm for 5 min; heat to 230°C at 10°C / min.
[0064] Mechanical properties test: The tensile and bending properties are tested using a universal testing machine, and the tensile strength, elongation at break, etc. are measured according to the reference standard GB / T-1040.1-2018.
[0065] Result analysis:
[0066] It can be clearly seen from Example 1 and Comparative Examples 1 and 2 that solid phase thickening can increase the viscosity of the slices and its molecular weight without much change in the color value b; in Comparative Example 3, since the reaction monomer is FDCA, its esterification rate is slower than the BDO cyclization rate under low temperature conditions, resulting in a low esterification rate, and the molecular weight of the slices obtained by the final polycondensation is extremely low; in Examples 4 and 5, the esterification temperature, alcohol-acid ratio and esterification liquid output when FDCA is used as a monomer are increased, and PBF slices are successfully prepared, but their color is darker, and the viscosity of the slices obtained by further solid phase thickening is not significantly increased. This is because under high temperature esterification conditions, FDCA decarboxylation is relatively more, BDO cyclization is accelerated, and other side reactions, resulting in the inability to further increase the molecular weight and deepen the color. It can be seen from Examples 1-5 that the most suitable ratio is 1.6, and the esterification rate is low when it is lower than 1.6. In Example 2, the esterification rate is too low, resulting in failure of normal polycondensation in the later stage. When it is higher than 1.6, the viscosity of the slices is not significantly increased. Considering the economic aspect, the best ratio is 1.5; it can be concluded from Examples 6-9 that the preferred catalyst is triphenyl phosphite and the antioxidant is B215; it can be seen from Examples 10-11 that the optimal polycondensation temperature is 220°C, too low a temperature cannot achieve the polycondensation conditions, too high a temperature leads to the loss of the end groups of the polycondensation monomers, and thermal decomposition occurs, resulting in a darker color and a low molecular weight of the obtained slices; in Examples 12-15, the viscosity-increasing time needs to be extended when the temperature is low, and the slices are prone to adhesion and a darker color when the temperature is too high; considering the economic cost, the best process for solid-phase viscosity-increasing is Example 1.
[0067] Depend on Figure 1 and Figure 2 It can be seen that the final furan ring polyester (PBF) has an initial thermal decomposition temperature of about 370.93°C, a crystallization temperature of about 108.40°C, and a glass transition temperature of about 41.51°C. It has good thermal stability and can exist stably under high-temperature processing conditions. Its tensile properties are relatively superior and can be further applied in spinning and other directions, and has great market potential.
[0068] It can be seen that the furan ring polyester (PBF) obtained in Example 1 can obtain polyester chips with large molecular weight, good color and high toughness, and effectively reduce side reactions such as BDO cyclization and FDCA decarboxylation, reduce the proportion of alkyd acid, reduce the waste of BDO, and the whole process is simple and efficient, achieving the experimental purpose.
[0069] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a furan-based high molecular weight polyester with excellent toughness, characterized in that: The steps include: S1: preparing low molecular weight furan ring polyester; specifically: S11: adding a certain amount of furan ring-containing dibasic lipid and aliphatic diol as raw materials into a reaction container, adding an antioxidant and a catalyst, purging with nitrogen, and heating to 130-190° C. and stirring evenly, and maintaining a rotation speed of 80-120 rpm; S12: maintaining the temperature, reacting for 0.5-3h and maintaining the esterification under normal pressure, and collecting the obtained esterification liquid; S13: When the weight of the obtained esterified liquid reaches 1.5-3.2 times of the theoretical liquid output, the esterification is completed; S14: Start to evacuate the air, the pressure is less than -8KPa within 5 minutes and the evacuation is continued. After the pressure is evacuated to below -100Pa, the temperature is raised to 200-240℃; S15: maintaining the vacuum less than -70 Pa, reacting for 2-4 hours, reducing the speed to 10-30 rpm and reacting for 10-20 minutes, introducing nitrogen to a weak positive pressure after the reaction, discharging, cutting and drying to obtain a furan ring polyester with a lower molecular weight; S2: Preparation of high molecular weight furan ring polyester by solid phase viscosity enhancement; specifically: The furan ring polyester with a lower molecular weight obtained in step S1 is added to a reaction kettle. Under certain temperature and rotation speed conditions, an inert gas is continuously introduced, and the temperature is consistent with the temperature in the kettle. The reaction is carried out for 10-24 hours. After the discharge is cooled, a furan ring polyester with a higher molecular weight is obtained.
2. The method for preparing a furan-based high molecular weight polyester with excellent toughness according to claim 1, characterized in that: The furan ring-containing dibasic lipid is one of 2,5-furandicarboxylic acid methyl ester and 3,4-furandicarboxylic acid methyl ester.
3. The method for preparing a furan-based high molecular weight polyester with excellent toughness according to claim 1, characterized in that: The aliphatic diol is one or a mixture of ethylene glycol, propylene glycol, butylene glycol and hexylene glycol.
4. The method for preparing a furan-based high molecular weight polyester with excellent toughness according to claim 1, characterized in that: The antioxidant is one of 168, 626, B215, 1010, and 1098 or a combination thereof.
5. The method for preparing a furan-based high molecular weight polyester with excellent toughness according to claim 1, characterized in that: The catalyst is one or more of triphenyl phosphite, titanium glycolate, zinc acetate, phosphoric acid, phosphorous acid, and phosphate.
6. The method for preparing a furan-based high molecular weight polyester with excellent toughness according to claim 1, characterized in that: In step S11, the molar ratio of the aliphatic diol to the furan ring-containing dibasic lipid substance is (1.2-2.5):
1.
7. The method for preparing a furan-based high molecular weight polyester with excellent toughness according to claim 1, characterized in that: In step S11, the amount of the antioxidant is 0.1-5‰ based on the weight ratio of the furan ring-containing dibasic lipid; the amount of the catalyst is 0.1-5% based on the weight ratio of the furan ring-containing dibasic lipid.
8. The method for preparing a furan-based high molecular weight polyester with excellent toughness according to claim 1, characterized in that: In step S2, the temperature and rotation speed conditions are: 120-180°C and 80-120 rpm.
9. The method for preparing a furan-based high molecular weight polyester with excellent toughness according to claim 1, characterized in that: In step S2, the inert gas is nitrogen at a rate of 5-8 L / min.
10. A furan-based high molecular weight polyester having excellent toughness, characterized in that: The method is prepared according to any one of claims 1 to 9.